Answer:
The solution set is the interval (-∞ , 6] OR {x : x ≤ 6}
Step-by-step explanation:
* Lets explain how to find the solution set of the inequality
- The inequality is 5x - 9 ≤ 21
∵ 5x - 9 ≤ 21
- At first add 9 to both sides of the inequality to separate x in one
side and the numbers in the other sides
∴ 5x - 9 + 9 ≤ 21 + 9
∴ 5x ≤ 30
- Lets divide both sides of the inequality by 5 to find the values of x
∴ (5x ÷ 5) ≤ (30 ÷ 5)
∴ x ≤ 6
- The solutions of the inequality is all real numbers smaller than
or equal to 6
∴ The solution set is the interval (-∞ , 6] OR {x : x ≤ 6}
- We can represent this inequality graphically to more understand
for the solution
- From the graph the solution set is the purple area
Which expression is equivalent to ((2a^-3 b^4)^2/(3a^5 b) ^-2)^-1
Answer:
[tex]\large\boxed{\dfrac{1}{36a^4b^{10}}}[/tex]
Step-by-step explanation:
[tex]\left(\dfrac{\left(2a^{-3}b^4\right)^2}{\left(3a^5b\right)^{-2}}\right)^{-1}\qquad\text{use}\ a^{-1}=\dfrac{1}{a}\\\\=\dfrac{\left(3a^5b\right)^{-2}}{\left(2a^{-3}b^4\right)^2}\qquad\text{use}\ (ab)^n=a^nb^n\\\\=\dfrac{3^{-2}(a^5)^{-2}b^{-2}}{2^2(a^{-3})^2(b^4)^2}\qquad\text{use}\ (a^n)^m=a^{nm}\\\\=\dfrac{3^{-2}a^{(5)(-2)}b^{-2}}{4a^{(-3)(2)}b^{(4)(2)}}=\dfrac{3^{-2}a^{-10}b^{-2}}{4a^{-6}b^8}\qquad\text{use}\ \dfrac{a^n}{a^m}=a^{n-m}[/tex]
[tex]=\dfrac{3^{-2}}{4}a^{-10-(-6)}b^{-2-8}=\dfrac{3^{-2}}{4}a^{-4}b^{-10}\qquad\text{use}\ a^{-n}=\dfrac{1}{a^n}\\\\=\dfrac{1}{3^2}\cdot\dfrac{1}{4}\cdot\dfrac{1}{a^4}\cdot\dfrac{1}{b^{10}}=\dfrac{1}{36a^4b^{10}}[/tex]
Answer:
1 / 36a^4 b^10
Step-by-step explanation:
the sum of 1/5 and twice a number is equal to 4/5 subtracted from three times the number. find the number.
Answer:
1
Step-by-step explanation:
Your equation may be written as follows:
[tex]\frac{1}{5} +2n=3n-\frac{4}{5}[/tex]
Start by multiplying both sides by 5 to clear your fractions.
[tex]\frac{1}{5} +2n=3n-\frac{4}{5} \\1+10n=15n-4[/tex]
Next, subtract 10n from both sides.
[tex]1+10n=15n-4\\1=5n-4[/tex]
Add 4 to both sides.
[tex]1=5n-4\\5=5n[/tex]
Divide both sides by 5 to solve for n.
[tex]5=5n\\1=n[/tex]
Final answer:
By setting up an equation 1/5 + 2x = 3x - 4/5 and solving for x, we find that the number is 1.
Explanation:
The problem involves finding a number when given a relationship involving fractions and that number. The relationship is: the sum of 1/5 and twice a number is equal to 4/5 subtracted from three times the number. To find the number, we set up an equation and solve for the variable, which represents the number.
Let's denote the number as x. Our equation can be written as:
1/5 + 2x = 3x - 4/5
We bring all the x terms on one side and the constants on the other to solve for x:
2x - 3x = -4/5 - 1/5
-x = -1
x = 1
true or false
x=3 when 5*6\x=10
A box contains 90 coins, only dimes and nickels. The amount of money in the box is $6.00. How many dimes and how many nickels are in the box?
The number of dimes is
The number of nickels is
Answer:
60 nickles and 30 dimes
Step-by-step explanation:
60 $0.05=3.00
30 $.10=3.00
60+30=90
In the box, there are 30 dimes and 60 nickels, as determined by solving a system of equations based on the total number of coins and their value.
Explanation:The box contains both dimes and nickels, totaling an amount of money of $6.00. Because a dime is worth $0.10 and a nickel is worth $0.05, we can set up a system of equations to solve this problem.
Let's denote the number of dimes as x and the number of nickels as y. Thus, our equations are x + y = 90 (since the total number of coins is 90) and 0.10x + 0.05y = 6 (since the total value of the coins is $6.00).
Solving these equations will give us the number of dimes and nickels in the box. Doubling the second equation gives us 0.20x + 0.10y = 12. We can subtract the first equation from this to solve for x, giving us x = 30. Substituting x=30 into the first equation, y = 90 - 30, so y = 60. So, there are 30 dimes and 60 nickels in the box.
Learn more about Systems of Equations here:https://brainly.com/question/35467992
#SPJ2
simplify (2x^4y^3) x (6x^3y^2)
Answer:
[tex]\large\boxed{(2x^4y^3)(6x^3y^2)=6x^7y^5}[/tex]
Step-by-step explanation:
[tex](2x^4y^3)(6x^3y^2)\\\\=(2)(3)(x^4x^3)(y^3y^2)\qquad\text{use}\ a^na^m=a^{n+m}\\\\=6x^{4+3}y^{3+2}\\\\=6x^7y^5[/tex]
120 is increased by d % and increased by 25% . What is the result ?
Please see attached image for complete answer and steps in detail.
Answer:
The result is 150 + 1.5d
Step-by-step explanation:
We want to translate the wordings into algebraic expression.
Firstly, we increase 120 by d%
d% = d/100
So increasing 120 by d % means;
120 + (d/100 * 120)
= 120 + 1.2d
Then increase this by 25%
= (120 + 1.2d) + 25/100(120 + 1.2d)
= 120 + 1.2d + (120+1.2d)/4
= 120 + 1.2d + 30 + 0.3d
= 120 + 30 + 1.2d + 0.3d
= 150 + 1.5d
Which graph shows the solution to the inequality |x+3| >2
Answer:
The answer is B, given the module of a number has always a positive value
Answer:
Answer is B.
SECOND NUMBER LINE
Step-by-step explanation:
Find the value of y.
Answer:
=6√3 the third option.
Step-by-step explanation:
We can use the Pythagoras theorem to find the value of y. We need two equations that include y.
a²+b²=c²
c=9+3=12
x²+y²=12²
x²=144 - y².........i (This is the first equation)
We can also express it in another way but let us find the perpendicular dropped to c.
perpendicular²= x²-3²=x²-9 according to the Pythagoras theorem.
y²=(x²-9)+9²
y²=x²+72
x²=y²-72....ii( this is the second equation
Let us equate the two.
y²-72=144-y²
2y²=144+72
2y²=216
y²=108
y=√108
In Surd form √108=√(36×3)=6√3
y=6√3
Which is the graph of the equation y = -3x- 1
Neither of those two graphs do the trick, but if I saw the rest of the answer choices, then I would be happy to assist you.
what’s the inverse function
Answer:
[tex]f^{-1}(x)=-2x+6[/tex].
Step-by-step explanation:
[tex]y=f(x)[/tex]
[tex]y=3-\frac{1}{2}x[/tex]
The biggest thing about finding the inverse is swapping x and y. The inverse comes from switching all the points on the graph of the original. So a point (x,y) on the original becomes (y,x) on the original's inverse.
Sway x and y in:
[tex]y=3-\frac{1}{2}x[/tex]
[tex]x=3-\frac{1}{2}y[/tex]
Now we want to remake y the subject (that is solve for y):
Subtract 3 on both sides:
[tex]x-3=-\frac{1}{2}y[/tex]
Multiply both sides by -2:
[tex]-2(x-3)=y[/tex]
We could leave as this or we could distribute:
[tex]-2x+6=y[/tex]
The inverse equations is [tex]y=-2x+6[/tex].
Now some people rename this [tex]f^{-1}[/tex] or just call it another name like [tex]g[/tex].
[tex]f^{-1}(x)=-2x+6[/tex].
Let's verify this is the inverse.
If they are inverses then you will have that:
[tex]f(f^{-1}(x))=x \text{ and } f^{-1}(f(x))=x[/tex]
Let's try the first:
[tex]f(f^{-1}(x))[/tex]
[tex]f(-2x+6)[/tex] (Replace inverse f with -2x+6 since we had [tex]f^{-1})(x)=-2x+6[/tex]
[tex]3-\frac{1}{2}(-2x+6)[/tex] (Replace old output, x, in f with new input, -2x+6)
[tex]3+x-3[/tex] (I distributed)
[tex]x[/tex]
Bingo!
Let's try the other way.
[tex]f^{-1}(f(x))[/tex]
[tex]f^{-1}(3-\frac{1}{2}x)[/tex] (Replace f(x) with 3-(1/2)x since [tex]f(x)=3-\frac{1}{2}x[/tex])
[tex]-2(3-\frac{1}{2}x)+6[/tex] (Replace old input, x, in -2x+6 with 3-(1/2)x since [tex]f(x)=3-\frac{1}{2}x[/tex])
[tex]-6+x+6[/tex] (I distributed)
[tex]x[/tex]
So both ways we got x.
We have confirmed what we found is the inverse of the original function.
Answer:
[tex]\laege\boxed{f^{-1}(x)=-2x+6}[/tex]
Step-by-step explanation:
[tex]f(x)=3-\dfrac{1}{2}x\to y=3-\dfrac{1}{2}x\\\\\text{Exchange x to y and vice versa:}\\\\x=3-\dfrac{1}{2}y\\\\\text{Solve for}\ y:\\\\3-\dfrac{1}{2}y=x\qquad\text{subtract 3 from both sides}\\\\-\dfrac{1}{2}y=x-3\qquad\text{multiply both sides by (-2)}\\\\\left(-2\!\!\!\!\diagup^1\right)\cdot\left(-\dfrac{1}{2\!\!\!\!\diagup_1}y\right)=-2x-3(-2)\\\\y=-2x+6[/tex]
John was 40 years old in 1995 while his father was 65.In what year was John exactly half his father's age?
Answer:
1980.
Step-by-step explanation:
John was born in 1995 - 40 = 1955.
His father was born in 1995 - 65 = 1930.
Let x be Johns age and his father 2x
1955 + x = 1930 + 2x
1955 - 1930 = 2x - x
x = 25
So the year is 1955 + 25 = 1980..
In that year John was 25 and his father was 50.
Which one of the following is equal to 1hector area? 10000m/square 10000m/square 100m/square
100000m/square
Answer:
10,000 m/square
Step-by-step explanation:
we know that
A hectare is a unit of area equal to [tex]10,000\ m^{2}[/tex]
The symbol is Ha
Verify each case
case 1) 10,000 m/square
The option is true
case 2) 100 m/square
The option is false
case 3) 100,000 m/square
The option is false
Find the equation of the axis of symmetry and the coordinates of the vertex of the graph of the function y = 2x2 + 4x –3.
Answer:
Equation of the parabola: [tex]y = 2x^{2} + 4x - 3[/tex].
Axis of symmetry: [tex]x= -1[/tex].
Coordinates of the vertex: [tex]\displaystyle \left(-1, -5\right)[/tex].
Step-by-step explanation:
The axis of symmetry and the coordinates of the vertex of a parabola can be read directly from its equation in vertex form.
[tex]y = a(x-h)^{2} +k[/tex].
The vertex of this parabola will be at [tex](h, k)[/tex]. The axis of symmetry will be [tex]x = h[/tex].
The equation in this question is in standard form. It will take some extra steps to find the vertex form of this equation before its vertex and axis of symmetry can be found. To find the vertex form, find its coefficients [tex]a[/tex], [tex]h[/tex], and[tex]k[/tex].
Expand the square in the vertex form using the binomial theorem.
[tex]y = a(x-h)^{2} +k[/tex].
[tex]y = a(x^{2} - 2hx + h^{2}) +k[/tex].
By the distributive property of multiplication,
[tex]y = (ax^{2} - 2ahx + ah^{2}) +k[/tex].
Collect the constant terms:
[tex]y = ax^{2} - 2ahx + (ah^{2} +k)[/tex].
The coefficients in front of powers of [tex]x[/tex] shall be the same in the two forms. For example, the coefficient of [tex]x^{2}[/tex] in the given equation is [tex]2[/tex]. The coefficient of [tex]x^{2}[/tex] in the equation [tex]y = ax^{2} - 2ahx + (ah^{2} +k)[/tex] is [tex]a[/tex]. The two coefficients need to be equal for the two equations to be equivalent. As a result, [tex]a = 2[/tex].
Similarly, for the term [tex]x[/tex]:
[tex]-2ah = 4[/tex].
[tex]\displaystyle h = -\frac{2}{a} = -1[/tex].
So is the case for the constant term:
[tex]ah^{2} + k = -3[/tex].
[tex]k = -3 - ah^{2} = -5[/tex].
The vertex form of this parabola will thus be:
[tex]y = 2(x -(-1))^{2} + (-5)[/tex].
The vertex of this parabola is at [tex](-1, -5)[/tex].
The axis of symmetry of a parabola is a vertical line that goes through its vertex. For this parabola, the axis of symmetry is the line [tex]x = -1[/tex].
which value is equivalent to (7x5x2/7x3)^2 x (5^0/2^-3)^3 x2^-9?
Answer:
100/9
Step-by-step explanation:
(7*5*2/7*3)² * (5^0/2^-3)³ * 2^-9
Solution:
We know that any number with power 0 = 1
(7*5*2/7*3)² * (1/2^-3)³ * 2^-9
Now cancel out 2 by 2
= (7*5*2/7*3)² * (1/1^-3)³ * 1^-9
=(70/21)² * (1)³/(1^-3)³ * 1^-9
=(10/3)^2 * 1/1^-1 * 1/1^9
=100/9 *1 *1
=100/9....
Determine whether the relation represents y as a function of x.
In ΔBCA, CA = 15 cm, CF = 7 cm, BH = 3 cm. Find the perimeter of ΔBCA.
25 cm
35 cm
36 cm
46 cm
Answer:
The perimeter of the triangle is equal to 36 cm
Step-by-step explanation:
we know that
The inscribed circle contained in the triangle BCA is tangent to the three sides
we have that
BF=BH
CF=CG
AH=AG
step 1
Find CG
we know that
CF=CG
so
CF=7 cm
therefore
CG=7 cm
step 2
Find AG
we know that
CA=AG+CG
we have
CA=15 cm
CG=7 cm
substitute
15=AG+7
AG=15-7=8 cm
step 3
Find AH
Remember that
AG=AH
we have
AG=8 cm
therefore
AH=8 cm
step 4
Find BF
Remember that
BF=BH
BH=3 cm
therefore
BF=3 cm
step 5
Find the perimeter of the triangle
P=AH+BH+BF+CF+CG+AG
substitute the values
P=8+3+3+7+7+8=36 cm
The perimeter of ΔBCA (triangle BCA) is 36 cm
Perimeter of a triangle
The perimeter of a triangle is the sum of the length of the three sides.
The inscribed circle contained in the triangle BCA is tangent to the three sides
Therefore,
BF = BH = 3 cm
CF = CG = 7 cm
AH = AG = 15 - 7 = 8 cm
Therefore,
perimeter = CA + BC + BA
perimeter = 15 + 3 + 7 + 3 + 8
Therefore,
perimeter = 15 + 10 + 11
perimeter = 15 + 21
perimeter = 36 cm
learn more on perimeter here: https://brainly.com/question/15450681
Convert -sqrt3 - i to polar form. PLEASE HELP. Photo has more information
Answer:
-√3 - i ⇒ (2 , 7/6 π)
Step-by-step explanation:
* Lets explain how to convert a point in Cartesian form to polar form
- Polar coordinates of a point is (r , θ).
- The origin is called the pole, and the x axis is called the polar axis,
because every angle is dependent on it.
- The angle measurement θ can be expressed in radians or degrees.
- To convert from Cartesian Coordinates (x , y) to Polar
Coordinates (r , θ)
1. r = √( x² + y² )
2. θ = tan^-1 (y/x)
* Lets solve the problem
∵ The point in the Cartesian form is z = -√3 - i, where -√3 is the real
part and -i is the imaginary part
∴ The x-coordinate of the point is -√3
∴ The y-coordinate of the point is -1
∵ Both the coordinates are negative
∴ The point lies on the 3rd quadrant
- To convert it to the polar form find r and Ф
∵ [tex]r=\sqrt{x^{2}+y^{2}}[/tex]
∵ x = -√3 and y = -1
∴ [tex]r=\sqrt{(-\sqrt{3}) ^{2}+(-1)^{2}}=\sqrt{3+1}=\sqrt{4}=2[/tex]
∵ Ф = [tex]tan^{-1}\frac{y}{x}[/tex]
∴ Ф = [tex]\frac{-1}{-\sqrt{3}}=\frac{1}{\sqrt{3}}[/tex]
- The acute angle π/6 has tan^-1 (1/√3)
∵ The point is in the third quadrant
∴ Ф = π + π/6 = 7/6 π
- Lets write it in the polar form
∴ -√3 - i ⇒ (2 , 7/6 π)
Answer:
2cis 7pi/6
Step-by-step explanation:
In the Pythagorean Theorem, what
does the "a" stand for?
a2 + b2 = c2
A. The longest side, or hypotenuse, of a right triangle.
B. One of the sides, or legs, that make up the right
angle.
C. Any unknown side of a right triangle.
Answer:
B. One of the sides, or legs, that make up the right angle.
Step-by-step explanation:
The Pythagoras Theorem applies to the right-angled triangles. It is basically a relationship between the sizes of the all lengths of the triangle. The Pythagoras Theorem is given by:
C^2 = A^2 + B^2; where A and B are perpendicular and base respectively, and C is the hypotenuse. It is interesting to note that A can either be the perpendicular or the base of the right angled triangle. Same goes for B; it can be either the perpendicular or the base. Both the perpendicular and the base intersect at 90 degrees. But both cannot be the hypotenuse. Therefore, the variable A in the Pythagoras Theorem is one of the sides, or legs, that make up the right angle, i.e. Option B is the correct answer!!!
Global online music sales have exploded. It was expected that music lovers would spend 2 billion for online music in 2007, in scientific notation this number is?
Pls help ive been struggling on this for a while
Answer:
[tex]2*10^{9}[/tex]
Step-by-step explanation:
we know that
One billion is equal to one thousand million
1 billion is equal to 1,000,000,000
so
Multiply by 2
2 billion is equal to 2,000,000,000
Remember that
In scientific notation, a number is rewritten as a simple decimal multiplied by 10 raised to some power, n
n is simply the number of zeroes in the full written-out form of the number
In this problem n=9
so
[tex]2,000,000,000=2*10^{9}[/tex]
The average car sold from Dealership A is $25,700. If the sales person receives 1.5% commission on the price of the car, how much commission is made on average per car sold?
Answer:
385.5 USD
Step-by-step explanation:
If an average car is sold for 25,700 USD, and the sales person gets 1.5% commission of it, we can easily get to the amount of money that the sales person managed to get from each sale.
The 25,700 should be divided by 100, as that is number of total percentage:
25,700 / 100 = 257
So we have 1% being 257 USD, but we need 1.5%, so we should multiple the 257 USD by 1.5%:
257 x 1.5 = 385.5
So we get a result of 385.5 USD, which is the amount the sales person makes from commissions on average per sold car.
Multiply (9-4i)(2+5i)
(9 - 4i)(2 + 5i)
To solve this question you must FOIL (First, Outside, Inside, Last) like so
First:
(9 - 4i)(2 + 5i)
9 * 2
18
Outside:
(9 - 4i)(2 + 5i)
9 * 5i
45i
Inside:
(9 - 4i)(2 + 5i)
-4i * 2
-8i
Last:
(9 - 4i)(2 + 5i)
-4i * 5i
-20i²
Now combine all the products of the FOIL together like so...
18 + 45i - 8i - 20i²
***Note that i² = -1; In this case that means -20i² = 20
18 + 45i - 8i + 20
Combine like terms:
38 - 37i
^^^This is your answer
Hope this helped!
~Just a girl in love with Shawn Mendes
a^-3 over a^-2b^-5 write without rational notation and move all terms to numerator
Answer:
[tex]\large\boxed{\dfrac{a^{-3}}{a^{-2}b^{-5}}=a^{-1}b^5}[/tex]
Step-by-step explanation:
[tex]\dfrac{a^{-3}}{a^{-2}b^{-5}}=a^{-3}\cdot\dfrac{1}{a^{-2}}\cdot\dfrac{1}{b^{-5}}\qquad\text{use}\ x^{-n}=\dfrac{1}{x^n}\\\\=a^{-3}\cdot a^2\cdot b^5\qquad\text{use}\ x^n\cdot x^m=x^{n+m}\\\\=a^{-3+2}b^5=a^{-1}b^5[/tex]
Sheila is looking at some information for the obstacle course she is interested in completing. The x-coordinate is the number of the obstacle, while the y-coordinate is the average time to complete the obstacle, measured in minutes.
(1, 8.25), (2, 9.075), (3, 9.9825), (4, 10.98075)
Help Sheila use an explicit formula to find the average time she will need for the 8th obstacle.
f(8) = 8.25(1.1)^8; f(8) = 17.685
f(8) = 8.25(1.1)^7; f(8) = 16.077
f(8) = 1.1(8.25)^7; f(8) = 2861345
f(8) = 1.1(8.25)^8; f(8) = 23606102
Answer:
f(8) = 8.25(1.1)^7; f(8) = 16.077
Step-by-step explanation:
In order to calculate the explicit formula we need to look at the y coordinates. All the options list the formula of a Geometric Sequence, so we will find which sequence defines the given coordinates:
The sequence is:
8.25, 9.075, 9.9825, 10.98075
f(1) = First term of the Sequence = 8.25
r = Common Ratio = Ratio of two consecutive terms = [tex]\frac{9.075}{8.25}[/tex] = 1.1
The explicit formula for a geometric sequence is:
[tex]f(n)=f(1)(r)^{n-1}[/tex]
Using the values, we get:
[tex]f(n)=8.25(1.1)^{n-1}[/tex]
For 8th term, we have to replace n by 8:
[tex]f(8)=8.25(1.1)^{8-1}\\\\ f(8)=8.25(1.1)^{7} \\\\ f(8)=16.077[/tex]
So, second option gives the correct answer: f(8) = 8.25(1.1)^7; f(8) = 16.077
Answer:
B // f(8) = 8.25(1.1)^7; f(8) = 16.077
Step-by-step explanation:
I'm Pretty Sure She's Got It ^^^
Write the slope-intercept form of the equation that passes through the point (2, 3) and is perpendicular to the line y = 5/8x - 4
Answer:
[tex]\large\boxed{y=-\dfrac{8}{5}x+\dfrac{31}{5}}[/tex]
Step-by-step explanation:
[tex]\text{The slope-intercept form of an equation of a line:}\\\\y=mx+b\\\\m-slope\\b-y-intercept[/tex]
[tex]\text{Let}\\\\k:y=m_1x+b_1\\\\l:y=m_2x+b_2\\\\l\ \perp\ k\iff m_1m_2=-1\to m_2=-\dfrac{1}{m_1}\\\\l\ \parallel\ k\iff m_1=m_2\\\\--------------------------[/tex]
[tex]\text{We have:}\\\\y=\dfrac{5}{8}x-4\to m_1=\dfrac{5}{8}\\\\\text{The slope of a perpendicular line:}\ m_2=-\dfrac{1}{\frac{5}{8}}=-\dfrac{8}{5}\\\\\text{The equation:}\\\\y=-\dfrac{8}{5}x+b\\\\\text{Put the coordinates of the point (2, 3) to the equation:}\\\\3=-\dfrac{8}{5}(2)+b\qquad\text{solve for}\ b\\\\3=-\dfrac{16}{5}+b\qquad\text{add}\ \dfrac{16}{5}\ \text{to both sides}\\\\\dfrac{15}{5}+\dfrac{16}{5}=b\to b=\dfrac{31}{3}\\\\\text{Finally:}\\\\y=-\dfrac{8}{5}x+\dfrac{31}{5}[/tex]
Classify the following triangle. Check all that apply.
Answer:
obtuse, isosceles
Step-by-step explanation:
We have two angles that have the same measure - that means two sides are equal length. That means the triangle is isosceles
We have one angle that is greater than 90 degrees - that tells us the triangle is obtuse
1. If x[tex]y^{2}[/tex] and xy are perfect squares, where x and y are positive integers, what is the smallest value of x + y?
Answer:
8
Step-by-step explanation:
xy^2 = k*k y^2 x = k * k so x has to be a perfect square.
xy is a perfect square which means that since x is a perfect square (see above) then y will have to be as well
There is nothing that prohibits x = 4 and y = 4 as being the answer where x = y.
I think the smallest possible value for x + y is 8.
This excludes any possibility of 1 or 0 in some combination, although I would look into 1.
The length of a rectangle frame is represented by the expression 2x +8, and the width of the rectangle frame is represented by the expression 2x +6 what is the width of the rectangle frame that has a total area of 160 Square inches
Final answer:
The width of the rectangle frame with a total area of 160 square inches, and expressions for length (2x + 8) and width (2x + 6), is found to be 10 inches.
Explanation:
To solve for the width of the rectangle frame with an area of 160 square inches, where the length is represented by 2x + 8 and the width by 2x + 6, we need to set up an equation using the formula for the area of a rectangle, which is length × width. With the given area of 160 square inches, the equation is:
(2x + 8)(2x + 6) = 160
Let's expand this and solve for x:
4x² + 12x + 16x + 48 = 160
4x² + 28x + 48 = 160
4x² + 28x - 112 = 0
Divide everything by 4 to simplify:
x²+ 7x - 28 = 0
Factor this quadratic equation:
(x + 14)(x - 2) = 0
x = -14 or x = 2
Since a width cannot be negative, x = 2
Now, to find the width, replace x in the width expression:
Width = 2x + 6
Width = 2(2) + 6 = 4 + 6 = 10 inches
Thus, the width of the rectangle frame is 10 inches.
What was done to the quadratic parent function F(x) = x2 to get the
function G(x) = x2 - 3? 0)
A.Shifted 3 units to the right
B. Vertically stretched by multiplying by 3
C.Shifted 3 units down
D.Shifted 3 units to the left
ОА ОВ Oc OD
HINT
SUBMIT
Answer:
Option C.
Step-by-step explanation:
If k<0, the function g(x) = f(x) + k represents the function f(x) shifted k units downwards.
In this case, given that k=-3 (k<0). The graph was shifted 3 units down. Therefore, the correct option is Option C.
Audrey has x pounds of red grapes and y pounds of
green grapes. She has less than 5 pounds of grapesin
all.
Which are reasonable solutions for this situation?
Check all that apply.
D(-1,2)
(1.3.5)
D (2, 2)
(4.5, 0.5)
(5,0)
Answer:
(2,2)
Step-by-step explanation:
Which terms could be used as the first term of the expression below to create a polynomial written in standard form? Check all that apply.
+ 8r2s4 – 3r3s3
s5
3r4s5
–r4s6
–6rs5
Answer:
[tex]3r^{4}s^{5}\\-r^{4}s^{6}[/tex]
Step-by-step explanation:
The standard form of a polynomial is when its term of highest degree is at first place.
In this case, we have two variables. The grade of each term is formed by the sum of its exponents. That means both given terms have a degree of six. So, the right answers must have a higher degree.
Therefore, the right answers are the second and third choice, because their degrees are 9 and 10 respectively.